Fiona gets the sniffles - Cowdrey, Richard; Wu, Donald (2023)
Fiona the hippo and her friends Cheetah, Chicken, and Fox figure out how to help sniffily Mr. Elephant feel better.
Keywords: Fiona -- (Hippopotamus), -- 2017- -- Fiction; Sick -- Fiction; Helpfulness -- Fiction; Hippopotamuses -- Fiction; Zoo animals -- Fiction; EDUCATION / Home Schooling; JUVENILE FICTION / Animals / Hippos & Rhinos; Animal fiction; Picture books